1996
DOI: 10.1021/bi960648h
|View full text |Cite
|
Sign up to set email alerts
|

Deacylation and Reacylation for a Series of Acyl Cysteine Proteases, Including Acyl Groups Derived from Novel Chromophoric Substrates

Abstract: In order to investigate structure-reactivity relationships within a series of acyl cysteine proteases [Doran, J. D., & Carey, P. R. (1996) Biochemistry 35, 12495-12502], deacylation kinetics have been measured for a number of acyl intermediates involving members of the papain superfamily. Derivatives of the "simple" chromophoric ligand (5-methylthienyl)acrylate (5MTA) and those based on two chromophorically labeled derivatives of peptidyl substrates, viz., 2-[(N-acetyl-L-phenylalanyl)amino]-3-(5-methylthienyl)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Gly114 is the N-terminal residue of R-helix 114-121 whose positive pole is directed at the benzoyl CdO. The two amide backbone H-bonds plus a possible contribution from the helix dipole constitutes a sizable electron-withdrawing force (Hol, 1985;Aqvist et al, 1991;Baker & Hubbard, 1984;Sali et al, 1988;Nicholson et al, 1991;Doran et al, 1996;Doran & Carey, 1996). The significance of these interactions in dehalogenase catalysis is underscored by the conservation of the Phe64 loop and Gly114 R-helix among the three known dehalogenase sequences (Lai, 1996) and the sequences of the enzymes of the enoyl-CoA family (Babbitt et al, 1992;DunawayMariano & Babbitt, 1994;Muller-Newen et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Gly114 is the N-terminal residue of R-helix 114-121 whose positive pole is directed at the benzoyl CdO. The two amide backbone H-bonds plus a possible contribution from the helix dipole constitutes a sizable electron-withdrawing force (Hol, 1985;Aqvist et al, 1991;Baker & Hubbard, 1984;Sali et al, 1988;Nicholson et al, 1991;Doran et al, 1996;Doran & Carey, 1996). The significance of these interactions in dehalogenase catalysis is underscored by the conservation of the Phe64 loop and Gly114 R-helix among the three known dehalogenase sequences (Lai, 1996) and the sequences of the enzymes of the enoyl-CoA family (Babbitt et al, 1992;DunawayMariano & Babbitt, 1994;Muller-Newen et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…4-[ 18 O]HBA-CoA. Solid 4-CBA-CoA (10 mg) was dissolved in 1 mL of H 2 18 O (99.2%) and converted to 4-HBA-CoA by the addition of 31 µL of 4-CBA-CoA dehalogenase (in buffered H 2 16 O, 3.7 mg/mL; specific activity ) 1.5 units/ mg) to give 11.4 mM 4-CBA-CoA and 10 µM 4-CBA-CoA dehalogenase in 5 mM K + Hepes (pH 7.0) (96% H 2 18 O). After 6 h at 25 °C, the 4-[ 18 O]HBA-CoA was purified by gel filtration chromatography (Sephadex G-25 column, 110 × 2.2 cm) using H 2 O as an eluant.…”
Section: Methodsmentioning
confidence: 99%
“…It is also recognized that the field can bring about a red shift in the absorption spectrum of a chromophoric group bound near the R-helix's N terminus (12,13). In addition, it has been suggested that R-helix dipoles can contribute to catalytic rate enhancement (14), and recent Raman and absorption spectroscopic studies on a series of acyl cysteine proteases (15,16) have provided quantitative support for this notion. When chromophoric acyl groups bind to cysteine proteases, substantial red shifts, of up to 60 nm, occur, which can be accompanied by major changes in the acyl group's Raman spectrum (12).…”
mentioning
confidence: 99%
“…The Raman difference spectra for acyl cysteine proteases, supported by absorption spectral data, provided different insights from those uncovered for the serine analogs (11,35). Principally, these involve so-called -electron polarization; in the cysteine protease active sites there are strong electrostatic forces that bring about a major rearrangement of the -electrons in the acyl group.…”
Section: Evolving Technology Increases Applications In Enzymologymentioning
confidence: 99%
“…For this reason the ligand modes dominate the difference spectrum. When experiments involve ligands that scatter less intensely, protein features appear in the difference spectrum in both the positive and negative directions, and these are a source of information on changes in protein structure, although the interpretation of many of these features is still in its infancy (33, 34).The Raman difference spectra for acyl cysteine proteases, supported by absorption spectral data, provided different insights from those uncovered for the serine analogs (11,35). Principally, these involve so-called -electron polarization; in the cysteine protease active sites there are strong electrostatic forces that bring about a major rearrangement of the -electrons in the acyl group.…”
mentioning
confidence: 99%